Eksistensialisme dan Eskatologi dalam Gala Bunga Matahari: Kajian Filosofis - Aini, Nur; Siswanto, Siswanto (TECHNO-SOCIO EKONOMIKA, 2025)
This study analyzes the lyrics of Gala Bunga Matahari by Sal Priadi through a philosophical approach to explore the existential and eschatological values embedded within. The research aims to uncover the existential values and analyze the eschatological representations in the lyrics of Gala Bunga Matahari. The method employed is qualitative research based on a library study, with primary data consisting of the song lyrics and secondary data derived from literature on existentialism, Islamic eschatology, and the philosophy of art. The analysis involves identifying symbols and metaphors in the lyrics, which are then interpreted using philosophical theories such as the thoughts of Kierkegaard, Sartre, and Al-Ghazali. The results show that the lyrics reflect human longing and hope in facing the limitations of life, as explained by existentialism. Additionally, symbols such as the "milk river" and the promise of reunion depict the belief in eternal happiness in the afterlife, in line with the concepts of Islamic eschatology. This study affirms that art, particularly music, can serve as an effective medium for philosophical expression, bridging human emotions with abstract ideas. Its implication is that art can be utilized to foster profound reflections on life and spirituality.